PENGGUNAAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA PADA MATERI TITRASI ASAM BASA - F Fathurrahmaniah; Eva Nursa’ban; E Ewisahrani (GRAVITY EDU : Jurnal Pembelajaran dan Pengajaran Fisika, 2021)
This study aims to determine the improvement of students' conceptual understanding using guided inquiry models on acid-base titration material. This study used a one-group pretest-posttest design, using one group of subjects, conducted at SMA PGRI Bolo-Bima in class XI for the 2020/2021 school year. The results showed that the percentage of student completeness at the pretest was 20%, meaning that only 4 out of 20 students completed. While the post-test results are inversely proportional to the pretest results with the percentage of student completeness of 100% meaning that all 20 students are complete. The results of the analysis of student activity data were obtained through observations by two observers during learning activities, the percentage of the frequency of student activity that was most dominant performed by students was carrying out investigations (13.9%), listening to / paying attention to teacher explanations (10.5%), and conclusions. investigation results (9.20%). As well as the results of student responses obtained an overall average of 90% of students gave positive responses and as many as 10% gave negative responses. Based on the results obtained in this study, it can be concluded that the use of the guided inquiry learning model used can improve students' conceptual understanding of acid-base titration material. Keywords: Guided Inquiry and Concept Understanding